PENGARUH PROGRAM DANA DESA, KESEMPATAN, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PARTISIPASI MASYARAKAT DALAM PENGELOLAAN KEUANGAN DESA - Nanen Rahma Pramesti, Resti; Sofwan, Ali (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
This study aims to determine and analyze the influence of village fund programs, opportunities, and transformational leadership. This study uses quantitative research methods. The type of data used in this study is primary data. The population that is the object of this study is the village apparatus, BPD, and RW villages in Pakis Aji Jepara District with a total of 196 people. The sample in this study used a saturated sample. The data collection technique used a questionnaire measured using a Likert scale. The data analysis technique used is multiple linear regression analysis with the help of SPSS. The results of this study indicate that partially the variables of the village fund program, opportunities, and transformational leadership have a positive and significant effect on the variable of community participation in village financial management. Simultaneously, the village fund program, opportunities, and transformational leadership have a positive and significant effect on the variable of community participation in village financial management